2007
DOI: 10.1523/jneurosci.3489-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of Spared Corticospinal Axons Augments Connections with Ipsilateral Spinal Motor Circuits after Injury

Abstract: Activity-dependent competition shapes corticospinal (CS) axon outgrowth in the spinal cord during development. An important question in neural repair is whether activity can be used to promote outgrowth of CS axons in maturity. After injury, spared CS axons sprout and make new connections, but often not enough to restore function. We propose that electrically stimulating spared axons after injury will enhance sprouting and strengthen connections with spinal motor circuits. To study the effects of activity, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
232
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(252 citation statements)
references
References 43 publications
(50 reference statements)
15
232
5
Order By: Relevance
“…Unilateral cortical injury or pyramidotomy also deprives the spinal cord unilaterally of direct cortical input. In adult rodents, sprouting of the CST from the intact side across the midline can be induced by suppression of the neurite growth inhibitor Nogo pathway (Thallmair et al, 1998;Wiessner et al, 2003), by local neurotrophic factors (Zhou and Shine, 2003), or by electrical stimulation of the injury-spared CST (Brus-Ramer et al, 2007). The rearranged CST is crucial for the observed recovery of skilled movements (Kartje-Tillotson et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral cortical injury or pyramidotomy also deprives the spinal cord unilaterally of direct cortical input. In adult rodents, sprouting of the CST from the intact side across the midline can be induced by suppression of the neurite growth inhibitor Nogo pathway (Thallmair et al, 1998;Wiessner et al, 2003), by local neurotrophic factors (Zhou and Shine, 2003), or by electrical stimulation of the injury-spared CST (Brus-Ramer et al, 2007). The rearranged CST is crucial for the observed recovery of skilled movements (Kartje-Tillotson et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of any resources on the paretic side, however, where ipsilesional motor systems are damaged beyond threshold level, harnessing contralesional activity may be partially adaptive through formation of atypical connections [60][61][62].…”
Section: Alternate Substrates and Their Role In Recovery: Contralesiomentioning
confidence: 99%
“…One approach to facilitate motor recovery after neurotrauma is to target intact or spared pathways. For example, in a recent study published in The Journal of Neuroscience, spared corticospinal axons were chronically stimulated to strengthen their connections with spinal circuits in adult rats (Brus-Ramer et al, 2007). Results indicated that activity-dependent mechanisms facilitate plasticity of spared ipsilateral corticospinal axons after injury.…”
mentioning
confidence: 99%
“…For example, in a recent study published in The Journal of Neuroscience, spared corticospinal axons were chronically stimulated to strengthen their connections with spinal circuits in adult rats (Brus-Ramer et al, 2007). Results indicated that activity-dependent mechanisms facilitate plasticity of spared ipsilateral corticospinal axons after injury.In the study by Brus-Ramer et al (2007), the left pyramidal tract of adult rats was lesioned, abolishing corticospinal projections to the ipsilateral and contralateral spinal cord. In some rats, an electrode was placed over the right pyramidal tract to chronically stimulate spared corticospinal axons after lesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation